MATATAG Curriculum: Why Curriculum [must] Change? - Estrellado, Carie Justine (Journal of Interdisciplinary Perspectives, 2023)
Curriculum changes dovetail with societal needs and advancements. As the world evolves, the educational landscape adapts to prepare students effectively. Technological progress, globalization, political acumen, and shifts in societal values necessitate updates to curriculum content and paradigms. This paper stimulates a macro-sociological vista on the MATATAG curriculum in the Philippine context. This revised curriculum, effective from the school year 2024 to 2025, addresses challenges faced by the current K to 12 curriculum, including numerous contents, misplaced prerequisite learning competencies, social inequities, and imbalances in thinking demands. This paper advances discourse regarding the adaptation to humanized learning and addresses the shortcomings of existing systems. In essence, curriculum changes are not just a response to challenges but a proactive stance for the demands of ever-changing needs. Although the context of the MATATAG agenda is not a mere blank ideation, it can be considered a national movement. Undeniably, education cannot be put at stake here because it determines what and how the Philippine nation will become in the next generation.